The Effect of Electronic Banking Transactions on Banking Fee-Based Income: (A Study on Commercial Banking Companies in Indonesia Listed with the Financial Services Authority (OJK) for the 2021–2024 Period) - Megasari, Rita; Yulistina, Yulistina; Sari, Pipit Novila (LPPPIPublishing, 2026)
This study aims to analyze the effect of electronic banking transactions, consisting of ATM, Mobile Banking, and Internet Banking transactions, on Fee based income in Indonesian banks. The data used in this study were obtained from 10 conventional commercial banks listed on the Otoritas Jasa Keuangan (OJK) for the period 2021–2024, with a total of 40 observations. The analytical method employed is multiple linear regression using SPSS version 26. The SPSS analysis results show an adjusted R² value of 0.464, indicating that the independent variables explain 46.4% of the variation in Fee Based Income. The F-test results in an F-value of 65.962 with a significance level of 0.000 < 0.05, suggesting that ATM, Mobile Banking, and Internet Banking simultaneously have a significant effect on Fee Based Income. However, the t-test reveals that only Mobile Banking (t = 4.523; sig. = 0.000) and Internet Banking (t = 2.290; sig. = 0.028) have a positive and significant partial effect. In contrast, the ATM variable (t = 0.891; sig. = 0.379) does not have a significant effect. These findings indicate that digital banking services such as Mobile Banking and Internet Banking are playing an increasingly important role in enhancing banks’ non-interest income, while traditional ATM services appear to be declining in their effectiveness in contributing to such income.